Determination of performance parameters of vertical axis wind turbines in wind tunnel - Nguyen Van Bang; Rozehnal Dalibor (MATEC Web of Conferences, 2017)
The paper deals with the determination of the performance parameters of a small vertical axis wind turbines (VAWT), which operate by the utilization of drag forces acting on the blades of the turbine. The performance was evaluated by investigating the electrical power output and torque moment of the wind machine. Measurements were performed on the full-scale model and the experimental data are assessed and compared to other types of wind turbines, with respect to its purpose.